A new genomic taxonomy system for the Synechococcus collective. (23rd August 2020) - Salazar, Vinícius W.; Tschoeke, Diogo A.; Swings, Jean; Cosenza, Carlos A.; Mattoso, Marta; Thompson, Cristiane C.; Thompson, Fabiano L.
Summary: Cyanobacteria of the genus Synechococcus are major contributors to global primary productivity and are found in a wide range of aquatic ecosystems. This Synechococcus collective (SC) is metabolically diverse, with some lineages thriving in polar and nutrient‐rich locations and others in tropical or riverine waters. Although many studies have discussed the ecology and evolution of the SC, there is a paucity of knowledge on its taxonomic structure. Thus, we present a new taxonomic classification framework for the SC based on recent advances in microbial genomic taxonomy. Phylogenomic analyses of 1085 cyanobacterial genomes demonstrate that organisms classified as Synechococcus are polyphyletic at the order rank. The SC is classified into 15 genera, which are placed into five distinct orders within the phylum Cyanobacteria: (i) Synechococcales ( Cyanobium, Inmanicoccus, Lacustricoccus gen. Nov., Parasynechococcus, Pseudosynechococcus, Regnicoccus, Synechospongium gen. nov., Synechococcus and Vulcanococcus ); (ii) Cyanobacteriales ( Limnothrix ); (iii) Leptococcales ( Brevicoccus and Leptococcus ); (iv) Thermosynechococcales ( Stenotopis and Thermosynechococcus ) and (v) Neosynechococcales ( Neosynechococcus ). The newly proposed classification is consistent with habitat distribution patterns (seawater, freshwater, brackish and thermal environments) and reflects the ecological and evolutionary relationships of the SC.